Odpowiedź :
Odpowiedź:
x³ +2 x² -3 x - 10 = 0
x = 2 bo 2³ + 2*2² -3*2 - 10 = 0
więc można podzielić przez x - 2
(x³ +2 x² -3 x - 10 ) : ( x - 2) = x² + 4 x + 5
- x³ + 2 x²
--------------
4 x² -3 x
-4 x² + 8 x
---------------------
5 x - 10
- 5 x + 10
--------------
0
x² + 4 x + 5 = 0 Δ = 16 - 4*1*5 < 0 - brak innych pierwiastków
Odp. x = 2
==========
x³- 19 x + 30 = 0
x = 2 bo 2³ - 19*2 + 30 = 0
-------
oraz ( x³ - 19 x + 30 ) : ( x - 2) = x² +2 x - 15
Δ = 4 -4*1*(-15) = 64 √Δ = 8 > 0
x² +2 x - 15 = ( x + 5)*( x - 3) = 0
x = -5 lub x = 3
----------------------
Zamiast x³ + 4 x² + x + 6 = 0 powinno być x³ +4 x² + x - 6 = 0
Wtedy x = - 3
( x³ + 4 x² + x - 6 ) : ( x + 3) = x² + x - 2
x² + x - 2 = ( x + 2)*( x - 1) = 0
oraz x = - 2 lub x = 1
----------------------------------------
Szczegółowe wyjaśnienie: